The Effect of Nutrition Counseling Using Whatsapp and MyfitnessPal Application on Vegetable and Fruit Consumption in Overweight and Obese Students - Ulfah Mahardika Pramono Putri (Fakultas Kesehatan, Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Overweight and obesity are the fifth-leading causes of death around the globe. One of the causes of these health problems is the need for a diet high in vegetables and fruits. The average intake of vegetables in the Special Region of Yogyakarta, such as Kulon Progo, was 2%, Bantul 1.7%, Sleman 1.8%, and the city of Yogyakarta 1.6%, respectively. Meanwhile, the average fruit consumption in Kulon Progo was 0.8%; in Sleman, it was 0.7%; in Yogyakarta, it was 0.8%; and in Bantul, it had declined. So, interventions are needed, such as nutritional counseling and intake monitoring, to boost the consumption of vegetables and fruits. The aim is to examine the effect of nutritional advice using WhatsApp and MyFitnessPal apps on vegetable and fruit consumption among overweight and obese students. A pretest-post-test study design with a control group design was used. The study population was students of Alma Ata University. The sample size was 78 overweight and obese students, employing a purposeful sampling technique and collecting data using analytical scales for weight factors and food intake using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ). Data analysis approaches used paired t-tests, Wilcoxon, and Mann-Whitney tests. Two times, dietary advice is given online via WhatsApp phone call. Based on the test results, the difference before and after counseling indicated insignificant results, with P = 0.663 on vegetable intake and P = 0.268 on fruit consumption. There is no effect of nutrition counseling using WhatsApp and MyFitnessPal application on vegetable and fruit consumption in overweight and obese students.